The Influence Of Perception On Purchasing Decision Of Soy Sauce Sachet In Rural And Urban Area - Hazrina Rachmawati; Istiqlaliyah Muflikhati (Journal of Consumer Sciences, 2017)
Nowadays. the soy sauce is sold in various of sizes plastic package from a large size to sachet. It is. therefore. very important to analyze the factors that influence the purchasing decision of soy sauce sachet. The study was conducted in Kebon Kalapa Subdistrict. Bogor  District as an urban area and Galuga Subdistrict. Bogor Disctrict as a rural area. One hundred and seventy-four households became the subject of the study and they were chosen by simple random sampling. The data were analyzed by using Chi-square. Independent sample t-test. Pearson correlation. and logistic regression. The result of the study showed that in rural area. the number of family members and price perception on purchasing decisions toward the soy sauce sachet influenced significantly. Overall. the price perception significantly influenced the purchasing decisions toward the soy sauce sachet.